(untitled) (Journal of Plant Disease Sciences, 2021)
A field experiment was carried out at the research farm of Pulse Research Unit, Washim Road Farm, Dr. Panjabrao Deshmukh Krishi Vidyapeeth, Akola during the winter season of 2019-20 on a vertisol soil, to study the response of chickpea (Cicer arietinum L.) to endomycorrhiza and lipo-chitooligosaccharides (LCO). Results indicated that seed inoculation with endomycorrhiza (4g) + lipo-chitooligosaccharides (0.33ml) kg/seed recorded the significantly higher number of root nodules per plant at 30 and 60 DAS, plant height, number of branches per plants and pods per plant in desi chickpea crop. The effect of seed inoculation treatment on microbial count (Spores/g soil @ x105) at 50% flowering, enzyme activity dehydrogenase and phosphatase were found significant. Seed inoculation with endomycorrhiza (4g) + lipo-chittooligodaccaride (0.33ml) recorded the significantly higher values of these parameters than the rest of the treatments. Similarly, the same treatment recorded significantly higher seed yield of desi chickpea.